PROPERTIES OF THE SAND-CLAY MIXTURES, CONTAINING COMPLEX BINDING MATERIAL - D. M. Kukuj; Ju. L. Lednev; I. B. Odarchenko (Литьë и металлургия, 2006)
It is determined that for compounds PGS being investigated the complex of requirements to the main technological quality parameters of mixture is provided at introduction of modificating compound.